Kurdish music in Turkey. (October 2019) - Alan, Suna
Musician and journalist Suna Alan gives an account of some of the songs she performs and loves. These are mainly Kurdish music. Suna describes the Dengbej tradition to which much of the music belongs. However, her summary of some songs, and excerpts from the lyrics, also draws on music by Sephardi Jews and the Armenians, other cultural groups who lived, like the Kurds, under the Ottoman Empire. The lyrics and Suna's contextualization of them in terms of the history they tell and from which they emerge reveal the oppression and suffering of these transcultural groups under the Ottoman Empire, but also their fight against injustice. The music remembers their loves as well as their losses.